Pengaruh Shopping Lifestyle, Fashion Involvement dan Hedonic Shopping Motivation terhadap Perilaku Impulse Buying - Puspitasari, Ayu; Telaumbanua, Septi Novita Sari (Politeknik Negeri Padang, 2022)
This study aims to determine how the influence of shopping lifestyle, fashion involvement, hedonic shopping motivation on impulse buying behavior. Where this research is motivated as a result of the high use of marketplace sites which causes people's behavior towards unplanned purchases (impulse buying) to also increase. The increase in impulse buying behavior in this study was influenced by 3 (three) factors, namely shopping lifestyle, fashion involvement, and hedonic shopping motivation. This research design uses an explanatory research approach and a quantitative descriptive analysis approach. The respondents of this research are people from the Batam city area who have used the Shopee application. And the number of respondents in this study were 100 people. The data analysis technique used is descriptive analysis and multiple linear regression analysis with testing using SPSS Version 20 software. The partial results show that shopping lifestyle, fashion involvement, has no significant effect on impulse buying behavior, while hedonic shopping motivation has an effect on impulse buying behavior. Meanwhile, the simultaneous testing of shopping lifestyle, fashion involvement, hedonic shopping motivation variables has an effect on impulse buying behavior